Trends in the place of death in Sweden from 2013 to 2019 – disclosing prerequisites for palliative care - Cecilia Larsdotter; Stina Nyblom; Hanna Gyllensten; Carl-Johan Furst; Anneli Ozanne; Ragnhild Hedman; Stefan Nilsson; Joakim Öhlén (Palliative Care and Social Practice, 2024)
Background: The drive for home care has increasingly impacted the organization and allocation of resources within the Swedish healthcare system. Objectives: With an interest in uncovering prerequisites for palliative care, this study aimed to investigate longitudinal trends in place of death within the adult Swedish population from 2013 to 2019 and examine potential associations between place of death and individual, geographic, and socioeconomic factors; hospital capacity; and healthcare utilization. Methods: This population-level comprehensive register study included all deceased individuals ⩾18 years old with a registered place of death ( n  = 599,137). Data were retrieved from public and patient data registers and the national register for palliative care. Trends and associations between place of death and co-variables were investigated by logistic regression- and interaction analyses. Results: From 2013 to 2019, the total number of home deaths increased by 1.9%, whereas the number of hospital deaths decreased by 2.6%. In the overall population of individuals living in their own homes, from 2013 to 2019, the likelihood of dying in hospital versus dying at home decreased (odds ratio: 0.98, 95% confidence interval: 0.97–0.99). Within the population with potential palliative needs living in their own home (78.4%), the likelihood of dying in hospitals equally decreased, except in Stockholm and the north region. For individuals residing in a nursing home, however, the likelihood of dying in hospital versus remaining in the nursing home until death only significantly decreased in the southern region. Conclusion: The results show a trend towards a decrease in hospital deaths but with cross-regional variations. Still, in 2019, only about one-fifth of all individuals died in their own homes. Public health-oriented interventions aimed at strengthening palliative care resources in nursing homes and home care are suggested.